PREVALENCE OF ISOLATED INCOMPLETE CLEFT LIP AMONG THE PATIENTS OF PRIVATE DENTAL COLLEGE - Subramanian, Vaishnavi Sivakali; Murugan P, Senthil; Kumar S, Aravind (International Journal of Psychosocial Rehabilitation, 2019)
Cleft lip and/ or palate are the most common facial congenital anomaly.Approximately 50% of cases born with cleft lip and palate occur due to a known genetic syndrome or with another malformation (e.g., congenital heart defects) and the other 50% occur as solitary defects, referred to often as non-syndromic clefts. Etiology for cleft lip or palate is multifactorial.Several in vitro studies have shown that the molecular pathways are responsible for proper closure of the palate, including the BMP, TGF-β, and SHH signaling pathways. Any disturbance in these pathways can cause clefting of lips or palate. In terms of environmental exposures, maternal tobacco smoke has been found to be strongly associated with cleft lips and palate. Some studies have suggested that maternal glucocorticoid exposure may also play a vital role. Isolated incomplete form of cleft lip is a rare form of cleft lip.There is a need for more epidemiologic studies to further investigate both etiology and treatment for isolated incomplete cleft lips as well as other types of cleft lips and palate. The objective of the study is to evaluate the prevalence of isolated incomplete cleft lip in patients reported to a private dental college.The patients with the diagnosis of cleft lip were randomly selected for the study. From the total sample size 86000 patients after implementing inclusion and exclusion criteria, a sample size of 27 patients were considered for this study. Compiled data was statistically analysed. In our study, isolated incomplete cleft lip was prevalent for only 33.3%.Whereas the other cleft lip which includes unilateral and bilateral cleft 66.7% together.Within the limitations, this study shows that there was only minimal prevalence of isolated incomplete cleft lip.Even though the prevalence of complete and incomplete cleft lip and palate are more common all over the world ,we felt that the incidence of isolated incomplete cleft lip is not least common,its prevalence of 33.3% is an indicator for performing further studies regarding its embryological and genetic basis.